ProductMeta: An Interactive System for Metaphorical Product Design Ideation with Multimodal Large Language Models - Zhou, Qinyi; Deng, Jie; Liu, Yu; Wang, Yun; Xia, Yan; Ou, Yang; Lu, Zhicong; Ma, Sai; Li, Scarlett; Xu, Yingqing (CHI 2025, 2025)
Product metaphors, which involve creating products that convey meaning through metaphorical associations, are a powerful tool in product design. However, according to our formative study, novice designers often struggle to establish coherent links between target and source, to manage the complexity of diverse mapping possibilities and to balance product usability with metaphorical expression. To address these challenges, we introduce ProductMeta, a creativity support tool designed to support novice designers in exploring and developing metaphorical product designs. ProductMeta incorporates domain knowledge and decomposes the design process into iterative modules and framework-based interfaces, fostering both divergent and convergent thinking. Through user studies, we demonstrate that ProductMeta enables novice designers to generate diverse and contextually relevant design ideas by facilitating structured exploration. We conclude with design implications for human-AI co-creation.